2019
DOI: 10.31557/apjcc.2019.4.4.131-133
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Carcinoma with Foci of Chondrosarcoma in Breast: A Rare Case

Abstract: Metaplastic carcinoma of breast is a rare form of tumour in which there is a mixture of malignant mesenchymal and epithelial elements. In these tumours cancerous cells of epithelial origin are found in combination with non-specific malignant spindle cells of mesenchymal origin. It is an aggressive form of cancer and usually appears in late stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This study presents clinical features, outcomes, and prognostic factors of forty patients of MBC, managed at our tertiary care institute. Generally, MBC presents with bigger size, higher grade and stage, triple negative hormone receptors with less metastasis to the lymph nodes and more possibility of distant metastasis when compared with Invasive Ductal Carcinoma (IDC) (Lai et al,2013;Vias et al,2019). Patients with MBC usually present at a median age of around 60 years (Rayson et al, 1999) while earlier diagnosis at the mean age of 50 years is also reported (Pitts et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study presents clinical features, outcomes, and prognostic factors of forty patients of MBC, managed at our tertiary care institute. Generally, MBC presents with bigger size, higher grade and stage, triple negative hormone receptors with less metastasis to the lymph nodes and more possibility of distant metastasis when compared with Invasive Ductal Carcinoma (IDC) (Lai et al,2013;Vias et al,2019). Patients with MBC usually present at a median age of around 60 years (Rayson et al, 1999) while earlier diagnosis at the mean age of 50 years is also reported (Pitts et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…These are usually CD 34 negative as it is positive in phyllodes, and sarcoma of the breast. Although mixed tumors are rare, there are case reports of MBC with cartilaginous differentiation with a co-existing foci chondrosarcoma with lympho-vascular invasion (Vias et al,2019).…”
Section: Discussionmentioning
confidence: 99%